2011
DOI: 10.3174/ajnr.a2880
|View full text |Cite
|
Sign up to set email alerts
|

Autism Attenuates Sex Differences in Brain Structure: A Combined Voxel-Based Morphometry and Diffusion Tensor Imaging Study

Abstract: BACKGROUND AND PURPOSE:It has been proposed that autism spectrums condition may represent a form of extreme male brain (EMB), a notion supported by psychometric, behavioral, and endocrine evidence. Yet, limited data are presently available evaluating this hypothesis in terms of neuroanatomy. Here, we investigated sex-related anatomic features in adults with AS, a "pure" form of autism not involving major developmental delay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
86
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(97 citation statements)
references
References 55 publications
(74 reference statements)
11
86
0
Order By: Relevance
“…Motivated by prior reports of white matter abnormalities at DTI in autism [20][21][22][23][24][25][26][27][28][29][30][31][32], we studied the analysis of the white matter with ADC to detect early regional brain abnormalities in autistic children and the measures their relation to clinical score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Motivated by prior reports of white matter abnormalities at DTI in autism [20][21][22][23][24][25][26][27][28][29][30][31][32], we studied the analysis of the white matter with ADC to detect early regional brain abnormalities in autistic children and the measures their relation to clinical score.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using diffusion tensor imaging (DTI), which assesses multiple aspects of molecular diffusion, have focused on parameters such as mean diffusivity (MD) and fractional anisotropy (FA). These studies reported a wide variety of abnormalities of MD and FA of autism at different regions of the brain including the frontal, temporal white matter and corpus callosum, but there is lack of consensus about the findings of these studies and there is lack of clinical correlation with social age, language age [20][21][22][23][24][25][26][27][28][29][30][31][32]. The novelty and uniqueness of this study is assessing the correlation of ADC value of different regions of the white matter with behavioral measures, CARS score, social age, and language age.…”
Section: Introductionmentioning
confidence: 94%
“…In general, previous studies found that females with autism show a differential expression of ASD compared to males with autism in terms of early brain overgrowth (Sparks et al, 2002), brain structure (Beacher et al, 2012a;Lai et al, 2013) and neural recruitment during task-based fMRI (Beacher et al, 2012b;Schneider et al, 2013).…”
Section: Introductionmentioning
confidence: 93%
“…One neuroanatomical study demonstrated that typical sexual dimorphisms in typical controls were absent or attenuated in males and females with ASD (Beacher et al, 2012a), whereas a more recent study identified significant alterations in grey and white matter in both sexes, but with minimal spatial overlap in the implicated regions in females and males (Lai et al, 2013). Also results from two task-based fMRI studies are supportive of a differential sex-specific expression of ASD, as revealed by opposite diagnosis-related effects in the two sexes; with females showing ASD-related hypo-activation (compared to typical females), and males showing hyper-activations (compared to typical males) during a mental rotation task (Beacher et al, 2012b) and empathy tasks (Schneider et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A multi-modality study [188] used the VBM and ROI analysis to estimate the GM and WM volumes from the sMRI and evaluate the main WM tracts in the DTI, respectively, for the ASP adults. The total WM volume, regional GM volume in the right parietal operculum, and FA in the body of the corpus callosum, cingulum, and cerebellum suggested a correlation between the diagnosis and subject's gender.…”
Section: B Tract-based Spatial Statistics (Tbss)mentioning
confidence: 99%